Conductive bridge random access memory - Goh, Zu Hong (Nanyang Technological University, 2024)
This paper outlines an exploration into the electrical behavior of conductive bridge random-access memory (CBRAM), featuring a Silver (Ag) top electrode (TE), with the switching layer comprised of Germanium Sulfide (GeS) and Molybdenum Disulfide (MoS2), while the bottom electrode (BE) utilises Platinum (Pt). The addition of MoS2 layer, which is a semiconducting 2D transition metal dichalcogenide (TMDs), has ion modulation properties which increases reliability of GeS-based CBRAM. The experimental results show bipolar resistive switching at higher compliance current (Icc) and threshold resistive switching at lower Icc. It also achieved Ion/Ioff ratio of 10^7, making it a great candidate for memory devices.